Pesquisadora de si: individuação e criação ritualística nas artes da cena - Vasconcelos, Bianca Adeltrudes de (2021)
The research entitled Researcher of the Self: Individuation and Ritualistic Creation in the Performing Arts walks through life and art, through ancestry and culture, carried by the author. The main objective of this study is to verify how research about oneself can contribute to the creative processes in the performing arts. In the search for paths that lead to a ritualistic scene, the creative artist weaves accounts of her own experiences (LARROSA, 2014) in the field of arts, using as her main source of inspiration the ancestry lived in the family setting. In this plot, the author sews real life, the processes of creation and the individuation process (JUNG, 1991) bringing to light the crossings caused on her life in a predominantly patriarchal universe. These accounts allow a rescue of the feminine and promote the researcher's encounter with herself in her body-house-memory that is supported by the mythology of the Triple Goddess and her faces. In order to create a dialogue between doing and thinking, the researcher weaves relationships with Ritual Theater (HADERCHPEK, 2020), with the work Mulheres que Correm com os Lobos (ÉSTES, 2014), and with A Jornada da Heroína (MURDOCK, 1990). From the tensions arising from the encounter of the body with the current structures and the everyday situations that make up being a woman, artist and teacher, a continuous reflection of the researcher on her own being emerges. This reflection allows the researcher to understand the plots that make up her life and evidence the dialogue with the collective and the practices that go through her.